Factors Affecting Health Service Utilization for Chronic Conditions: A Bibliometric Review of Primary Health Care - Sanni Rizky Putri; M. Bakhriansyah; Husaini Husaini; Musafaah Musafaah; Izaak Zoelkarnain (Malahayati Nursing Journal, 2024)
ABSTRACT Non-communicable diseases (NCDs) such as heart disease, diabetes and cancer are significant global health challenges, particularly in developing countries. Understanding healthcare utilization for NCDs is critical to improving healthcare outcomes and patient quality of life. This study aims to analyze trends and identify research gaps in healthcare utilization for NCDs through bibliometric analysis. With this approach, this study seeks to provide a comprehensive overview of research developments in this field and identify areas that require further attention. This study used bibliometric analysis with the Publish or Perish app and a Google Scholar search using the keywords "factors," "influences," "health service utilization," "non-communicable diseases," and "basic health services." From the search results, the top 50 journals from 2017 to 2024 were selected for analysis. The data were classified by year of publication, journal type, number of citations, and researcher country, and analyzed using VOSviewer to identify research patterns and gaps. The analysis showed that research was concentrated in highly ranked journals and developed countries, with key terms such as "non-communicable disease," "factor," "use," and "health." This research identifies gaps in implementation policies, innovative approaches, and healthcare utilization factors that are not yet fully understood. Understanding research trends and gaps can guide future research and policy development efforts to improve the effectiveness of interventions and policies in the management of NCDs globally. Keywords: Non-Communicable Diseases (NCDs), Health Service Utilization, Primary Health Care, Health Influencing Factors